Strategies for the Synthesis of Antifeedant Leucosceptroid Natural Products - Hugelshofer, Cedric L.; Magauer, Thomas (Synlett, 2015)
The evolving pathogen resistance in agricultural pests requires the development of novel chemical agents to maintain efficient pest control. Biological screening of natural products isolated from Leucosceptrum canum Smith led to the discovery of active antifeedant sesterterpenoids. This article highlights recent progress towards the synthesis of these natural products.1 Introduction2 Synthesis of the Leucosceptroid Core Structure3 Total Synthesis of Leucosceptroid B4 Towards the Collective Synthesis of Leucosceptroid Natural Products5 Total Synthesis of Leucosceptroids A and B6 Summary
Keywords: leucosceptroids; natural products; total synthesis; terpenoids; sesterterpenoids